Practicalities of Individual Producer Responsibility under the WEEE Directive - Vera Susanne Rotter; Perrine Chancerel; Wolf-Peter Schill (Waste Management and Research, 2011)
In theory, individual producer responsibility (IPR) creates incentives for "design-for-recycling". Yet in practice, implementing IPR is challenging, particularly if applied to waste electric and electronic equipment. This article discusses different options for implementing IPR schemes and producers' under German WEEE legislation. In addition, practical aspects of a German "return share" brand sampling scheme are examined. Concerning "new" WEEE put on the market after 13 August 2006, producers in Germany can choose between two different methods of calculating take-back obligations. These can be determined on the basis of "return shares" or "market shares". While market shares are regularly monitored by a national clearing house, the "return share" option requires sampling and sorting of WEEE. Herein itis shown that the specifics of the German WEEE take-back scheme require high sample sizes and multi-step test procedures to ensure a statistically sound sampling approach. Since the market share allocation continues to apply for historic waste, producers lack incentives for choosing the costly brand sampling option. However, even return share allocation might not imply a decisive step towards IPR, as it merely represents an alternative calculation of market shares. Yet the fundamental characteristics of the German take-back system remain unchanged: the same anonymous mix of WEEE goes to the same treatment operations. In the future, radio frequency identification-based sorting options could foster IPR and incentives for changes in product design.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; Individual producer responsibility (IPR); extended producer responsibility (EPR); waste electric and electronic equipment (WEEE); return share; brand sorting; collection; cost allocation; Umweltmanagement; Elektroindustrie; Abfallentsorgung; Deutschland